The Effect of Absorptive Capacity on Supply Chain Innovation Performance Through Supply Chain Agility in Manufacturing Companies in Bogor, Indonesia - Dewanti, Sabrina Ayu; Santosa, Wahyuningsih (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study examines the impact of absorptive capacity on supply chain innovation performance through supply chain agility in a manufacturing company in Bogor. Employing a quantitative approach, data were collected from 216 respondents via questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS. The results indicate that absorptive capacity positively influences supply chain agility (p-value = 0.000) but does not directly affect supply chain innovation performance (p-value = 0.318). Furthermore, supply chain agility also does not significantly affect innovation performance (p-value = 0.292). The study concludes that enhancing absorptive capacity can improve supply chain agility but does not necessarily translate into improved innovation performance. To address this, the company is advised to strengthen interdepartmental communication and optimize knowledge utilization in decision-making to enhance agility and innovation within the supply chain.